Huerta Ramírez, Pedro Gustavo. Participación política y revolución en China, Universidad Pedagógica y Tecnológica de Colombia, Tunja. Ediciones "La Rana y el Águila", 1977. 343 pp. - Montenegro, Leonardo (El Colegio de México, 1977)
-